Spiritualitas Islam dan Kepemimpinan Etis dalam Bisnis - Unti Ludigdo (Jurnal Aplikasi Manajemen, 2010)
Discussions about ethical leadership have eccessive done by various experts in many discipline. This is also done to explore the relationship- between religiousness/spirituality with leadership in the workplace. This issue is important to be studied, especially to find basically concept of ethical leadership in business. However, leadership in business has a power to force their organizational member (and their community) refer to ethical values. Related to it, this paper reveal how ethical leadership in buslness is developed based on substantive values of Islamic Pillars. Using reflexive-normative approach is found that Islamic Pillars have richness spiritual values. These spintual values of Islamic Pillars can be used to realize an ethical leadership in business.